KERAGAAN PERTUMBUHAN DAN PRODUKSI PADI SAWAH (ORYZA SATIVA L.) VARIETAS IR-64 DI TANAH GAMBUT YANG DIBERI DOLOMIT DAN TEMBAGA (CU) MELALUI DAUN - Idwar '; Sukemi Indra Saputra; Anthony Hamzah; Dahono '; Eliartati '; Zulkipli ' (Universitas Riau, 2004)
The study on growth production of paddy (Oryza sativa L.) Variety IR-64 in the peat soil given Dolomite andCopper (Cu) through leaves have been conducted at Simpang Baru Village Tampan, Pekanbaru City for 5bohths; starting from February to June 2003. The objective of the experiment was identity the effect ofbolomite and Copper given trough leaves and their interaction on the growth and pnKiuction of Rice in the peatisoil. The experiment was arranged in a randomized factorial block design with three replications. The firstfactor was various doses of Dolomite, that was KO (without Dolomite), K l (Dolomite of 0,5 ton/ha), K2 (Dolomiteof 1,0 ton/ha), K3 (Dolomite of 1,5 ton/ha), and K4 (Dolomite of 2,0 ton/ha). The second factor was various dosesof CuSO,, that was CO (without CuSO,), C I (CuSO, of 100 g/ha), C2 (CuSO^ of 200 g/Tta), C3 (CuSO, of 300g/lia), and C4 (CuSO, of 400 g/ha). Parameters observed were plant height, weight of drayed straw, number ofproductive samplings, percentage of well filled rice grain, weight of 1000 .seeds, weight of rice grain. Experi-ment result show tlrnt Dolomite could improve the growth and production of paddy rice and Chopper significantlyincreased weight of dried straw, percentage of well filled rice grain, weight of 1000 seeds and weight of ricegrain. The interaction between Dolomite and Copper significantly increased the weight of dried straw. Ricegrain production treated with 1,5 ton/ha Dolomite and CuSO^ 400 g/ha given trough leiives wiis 2,97 ton/ha.